Improving anxiety regulation in patients with breast cancer at the beginning of the survivorship period: a randomized clinical trial comparing the benefits of single‐component and multiple‐component group interventions. Issue 8 (7th November 2016) - Merckaert, Isabelle; Lewis, Florence; Delevallez, France; Herman, Sophie; Caillier, Marie; Delvaux, Nicole; Libert, Yves; Liénard, Aurore; Nogaret, Jean‐Marie; Ogez, David; Scalliet, Pierre; Slachmuylder, Jean‐Louis; et al.
Abstract: Objective: To compare in a multicenter randomized controlled trial the benefits in terms of anxiety regulation of a 15‐session single‐component group intervention (SGI) based on support with those of a 15‐session multiple‐component structured manualized group intervention (MGI) combining support with cognitive‐behavioral and hypnosis components. Methods: Patients with nonmetastatic breast cancer were randomly assigned at the beginning of the survivorship period to the SGI (n = 83) or MGI (n = 87). Anxiety regulation was assessed, before and after group interventions, through an anxiety regulation task designed to assess their ability to regulate anxiety psychologically (anxiety levels) and physiologically (heart rates). Questionnaires were used to assess psychological distress, everyday anxiety regulation, and fear of recurrence. Group allocation was computer generated and concealed till baseline completion. Results: Compared with patients in the SGI group (n = 77), patients attending the MGI group (n = 82) showed significantly reduced anxiety after a self‐relaxation exercise ( P  = .006) and after exposure to anxiety triggers ( P  = .013) and reduced heart rates at different time points throughout the task ( P  = .001 to P  = .047). The MGI participants also reported better everyday anxiety regulation ( P  = .005), greater use of fear of recurrence–related coping strategies ( P  = .022), and greater reduction in fear of recurrence–related psychological distress ( P  = .017) compared with the SGI group. Conclusions: This study shows that an MGI combining support with cognitive‐behavioral techniques and hypnosis is more effective than an SGI based only on support in improving anxiety regulation in patients with breast cancer.